Analisis Konsep Perbankan Syariah dalam Penggunaan E-Money - Cinta Rahmi; Srinandya Harum Caryarini; Ririn Dwi Prabandari; Muhammad Dzarres Jidan Al Ghiffari; Muhammad Ikhsan Fahmi; Ahmad Naufal (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research uses qualitative methods and literature study, by filling out questionnaires and analyzing related data. Qualitative methods can help provide clear research results. Qualitative methods are methods used to collect data. The aim of this research is to find out whether the existence of e-money, card payment tools, and Electronic Data Capture (EDC) machines influence the public in the concept of sharia banking.